[Steam Wells at Power Plant in Námaskarð] - Streng, Evelyn Fiedler (1975)
Photograph of steam wells at a power plant in Námaskarð. The grey, dusty field covers the foreground, lined by a wire fence in the bottom right corner and white pipes connecting to a yellow building in the middle ground. White steam covers the background, obscuring a brown and green mountain in the background.